The humanity of the music activity within Tocatas (Orfeu, 2017)
The purpose of this article is to trace the social and musical relevance of theevent known as “Tocata”, in Florianópolis/ SC. Proposed as an informal meeting,open and not restricted to musicians, theTocata opens itself as a shared experiencethat favors different potentialities of musical making, as well as the reinvention ofthe relationship that participants have withmusic. Given this specificity of the interactions and the human conviviality, as theyoccur there, the Tocata allows us an artistic-musical experience that occurs in thebecoming of a creative, simultaneous andcollective process, where the musical action intends to present itself in an affective,spontaneous and intuitive way. The data ofthe research is taken from reports of participants registered between 2015 and 2016for the Final Paper (TCC): ExperimentalConviviality and Musical Improvisation inthe Tocata: the production of an ethico--aesthetic attitude. We have placed thesereports in articulation with our own experience, as participants and researchersin the field of music and visual arts, andin dialogue with these fields we introducedescriptions of the Tocata and reflectionsthat have accompanied us during the lastyears.
Keywords: Tocata; Musical Meetings; Musical Improvisation; Creative process; Collaboration; Experience Reports